Preliminary investigation of experimental conditions and precision of an alternative method to determine high boiling point components in motor gasoline. (15th December 2016) - Zannikou, Y.; Karonis, D.; Mouzakis, A.
Abstract: This work describes a new method that can be used for the determination of high boiling point components in motor gasoline. Heavier components in the range of diesel fuel, if present in the gasoline, do not completely burn during the combustion cycle of spark ignition engines and increase exhaust emissions and deposits formation in the combustion chamber. The method used for the determination of heavy residue in gasoline is the atmospheric distillation test, according to EN ISO 3405 (similar to the classic ASTM D86) test method. The volume of distillation residue is recorded. This residue must be below 2% V/V according to EN 228 standard. The presence of heavy components is caused mainly by remnants in tanks and pipelines or bad housekeeping in the fuel distribution and supply chain. In this paper, a new alternative method is used. The residue is determined as mass percentage of the test sample after evaporation of a small quantity of the sample in a proper container put in an oven. Results show that at oven temperature of 220 °C and residence time of 20 min repeatable results can be obtained. The test method was also tested in gasoline sample that was intentionally mixed with automotive diesel, in concentrations up to 5% m/m, in an attempt to simulate a possible incident in the gasoline supply chain distribution system. Regarding the quantification of the amount of heavier fraction that was present in the fuel, the obtained results suggest that the new method gave better results in comparison to the classic EN ISO 3405 distillation test method.